Approaches in creating meta-requirement: a systematic literature review - Muhamad Idaham, Umar Ong; M. A., Ameedeen; Imran Edzereiq, Kamarudin (IOP Publishing, 2019)
Common development team will spend less resources on User Requirement Specification (URS) validation, in the case of development project that provides this URS in the phase of competing for tender. In order to overcome this, the use of meta-requirement in evaluation of requirements is being introduce. The purpose of this article is to present the finding of a systematic literature review of meta-requirements. A methodology that involve defining a systematic way of finding literature and presenting it in a meaningful manner has been adopted. Meta-requirement is an area that is station within the field of information system design theory which is contain in the design research body of knowledge. Based on the result of the analysis of the systematic literature review, it is shown that there is still advancement in the field of meta-requirement and there still improvement that can be done to further the knowledge and contribution in this area. It is suggested that further research that will define a highly comprehensive model of creating meta-requirement should be undergo and the issue of meta-requirement traceability against real-world requirements should be tackle.